Specificity of NifEN and VnfEN for the Assembly of Nitrogenase Active Site Cofactors in Azotobacter vinelandii - Ana Pérez-González (American Society for Microbiology, 2021)
ABSTRACT The nitrogen-fixing microbe Azotobacter vinelandii has the ability to produce three genetically distinct, but mechanistically similar, components that catalyze nitrogen fixation. For two of these components, the Mo-dependent and V-dependent components, their corresponding metal-containing active site cofactors, designated FeMo-cofactor and FeV-cofactor, respectively, are preformed on separate molecular scaffolds designated NifEN and VnfEN, respectively. From prior studies, and the present work, it is now established that neither of these scaffolds can replace the other with respect to their in vivo cofactor assembly functions. Namely, a strain inactivated for NifEN cannot produce active Mo-dependent nitrogenase nor can a strain inactivated for VnfEN produce an active V-dependent nitrogenase. It is therefore proposed that metal specificities for FeMo-cofactor and FeV-cofactor formation are supplied by their respective assembly scaffolds. In the case of the third, Fe-only component, its associated active site cofactor, designated FeFe-cofactor, requires neither the NifEN nor VnfEN assembly scaffold for its formation. Furthermore, there are no other genes present in A. vinelandii that encode proteins having primary structure similarity to either NifEN or VnfEN. It is therefore concluded that FeFe-cofactor assembly is completed within its cognate catalytic protein partner without the aid of an intermediate assembly site. IMPORTANCE Biological nitrogen fixation is a complex process involving the nitrogenases. The biosynthesis of an active nitrogenase involves a large number of genes and the coordinated function of their products. Understanding the details of the assembly and activation of the different nitrogen fixation components, in particular the simplest one known so far, the Fe-only nitrogenase, would contribute to the goal of transferring the necessary genetic elements of bacterial nitrogen fixation to cereal crops to endow them with the capacity for self-fertilization. In this work, we show that there is no need for a scaffold complex for the assembly of the FeFe-cofactor, which provides the active site for Fe-only nitrogenase. These results are in agreement with previously reported genetic reconstruction experiments using a non-nitrogen-fixing microbe. In aggregate, these findings provide a high degree of confidence that the Fe-only system represents the simplest and, therefore, most attractive target for mobilizing nitrogen fixation into plants.